The Effect of Shopping Experience, Interior Design, And Store Comfort on Customer Satisfaction at Casabella Store - Raymond Justine; Agusman; Mario Andriaskiton (PT Inovasi Pratama Internasional, 2026)
This study aims to analyse the influence of shopping experience, interior design, and store comfort on customer satisfaction at Casabella Store. This study uses a quantitative approach with an associative research design. The population in this study consisted of customers who had conducted shopping activities at Casabella Store. Since the exact population size was unknown, the researcher applied the Hair method in determining the sample size. A total of 150 questionnaires were distributed using accidental sampling techniques. Data were collected through questionnaires and analysed using multiple linear regression analysis with the assistance of Statistical Package for Social Sciences (SPSS). The results of the partial significance test showed that shopping experience has a positive but not significant effect on customer satisfaction with a tcount value of 1.192 and significance value of 0.235 (>0.05). Interior design has a positive and significant effect on customer satisfaction with a tcount value of 5.017 and significance value of 0.000 (<0.05). Store comfort also has a positive but not significant effect on customer satisfaction with a tcount value of 1.360 and significance value of 0.176 (>0.05). Simultaneously, shopping experience, interior design, and store comfort significantly influence customer satisfaction with an Fcount value of 10.804 and significance value of 0.000 (<0.05). The coefficient of determination test showed that the independent variables explain 16.5% of customer satisfaction, while the remaining 83.5% is influenced by other variables outside this study. These findings indicate that interior design is the most dominant factor influencing customer satisfaction at Casabella Store